2013
DOI: 10.1021/la402678j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of DNA-Templated Te and Bi2Te3 Nanowires by Galvanic Displacement

Abstract: This paper demonstrates the use of galvanic displacement to form continuous tellurium-based nanowires on DNA templates, enabling the conversion of metals, which can be deposited site-specifically, into other materials needed for device fabrication. Specifically, galvanic displacement reaction of copper and nickel nanowires is used to fabricate tellurium and bismuth telluride nanowires on λ-DNA templates. The method is simple, rapid, highly selective, and applicable to a number of different materials. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 59 publications
0
43
0
Order By: Relevance
“…Nevertheless, despite the rapid growth of applications for Ag N ‐DNA, it is not understood why certain sequences produce brightly fluorescent solutions while other apparently similar sequences do not. This question of the influence of biopolymer host sequence on the structure of templated inorganic particles is scientifically rich, with potential for high payoff if approaches can be developed to address the complexities introduced by sequence diversity and flexibility of polymeric templates. In the specific context of Ag N ‐DNA, robust design methods for DNA template strands are sorely needed to aid future applications development.…”
Section: Top 10 Most Frequently Occurring Discriminative Motifs As Imentioning
confidence: 99%
“…Nevertheless, despite the rapid growth of applications for Ag N ‐DNA, it is not understood why certain sequences produce brightly fluorescent solutions while other apparently similar sequences do not. This question of the influence of biopolymer host sequence on the structure of templated inorganic particles is scientifically rich, with potential for high payoff if approaches can be developed to address the complexities introduced by sequence diversity and flexibility of polymeric templates. In the specific context of Ag N ‐DNA, robust design methods for DNA template strands are sorely needed to aid future applications development.…”
Section: Top 10 Most Frequently Occurring Discriminative Motifs As Imentioning
confidence: 99%
“…Similar improvements in the zT of chalcogenides such as Bi 2 Te 3 and Bi x Sb 2 − x Te 3 , some of the best bulk thermoelectric materials, have also been modeled [385,386] and demonstrated experimentally [387,388]. These materials may be readily grown in nanowire morphology via templated electrodeposition [387,[389][390][391][392][393], with Bi 2 Te 3 nanowires also having been grown via galvanic displacement on DNA templates [394]. Increased zT has also been demonstrated in superlattice structures, such as PbTe/Te, PbTe/PbSe [395], and Bi 2 Te 3 [396] superlattice structures may be combined with nanowire morphologies via templated electrodeposition for potentially even greater gains in zT.…”
Section: Thermoelectricsmentioning
confidence: 74%
“…[53] Nevertheless, Harb and co-workers reported that DNAstabilized Ni or Cu nanowires reacted with HTeO 2+ ions or the mixture of HTeO 2+ and Bi 3+ ions by GR to produce Te or Bi 2 Te 3 nanowires. [54] The GR left the nanowire structure unchanged. In this study, continuous DNA-stabilized Ni and Cu nanowires were synthesized by seeding with Ag and electroless plating of Ni or Cu.…”
Section: Nanowiresmentioning
confidence: 99%